1990
DOI: 10.1029/jb095ib01p00341
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of pressure‐induced grain crushing in porous rocks

Abstract: The hydrostatic compaction behavior of a suite of porous sandstones was investigated at confining pressures up to 600 MPa and constant pore pressures ranging up to 50 MPa. These five sandstones (Boise, Kayenta, St. Peter, Berea, and Weber) were selected because of their wide range of porosity (5–35%) and grain size (60–460 μm). We tested the law of effective stress for the porosity change as a function of pressure. Except for Weber sandstone (which has the lowest porosity and smallest grain size), the hydrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
357
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 469 publications
(385 citation statements)
references
References 44 publications
27
357
1
Order By: Relevance
“…[5] However, the model derived by Wong and coworkers [Wong, 1990;Zhang et al, 1990] does not in itself lead to a strictly defined whole-grain failure criterion, as the porosity and grain size dependence of the critical effective pressure observed in compaction experiments is introduced to the model by relating the grain failure load to P cr on the basis of a random packing model and by assuming that the flaw dimension (at failure) scales linearly with grain size [see Zhang et al, 1990, equation 7]. In addition, this criterion does not directly offer an explanation for the grain size dependence of the grain failure load obtained from compaction experiments and single-grain crushing tests.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5] However, the model derived by Wong and coworkers [Wong, 1990;Zhang et al, 1990] does not in itself lead to a strictly defined whole-grain failure criterion, as the porosity and grain size dependence of the critical effective pressure observed in compaction experiments is introduced to the model by relating the grain failure load to P cr on the basis of a random packing model and by assuming that the flaw dimension (at failure) scales linearly with grain size [see Zhang et al, 1990, equation 7]. In addition, this criterion does not directly offer an explanation for the grain size dependence of the grain failure load obtained from compaction experiments and single-grain crushing tests.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on time-independent compaction of porous sandstones and sands at room temperature have shown irrecoverable porosity reduction during loading, which increases significantly beyond a specific critical effective pressure (P cr ) [Borg et al, 1960;Chuhan et al, 2003;Dunn et al, 1973;Karner et al, 2003Karner et al, , 2005Lambe and Whitman, 1969;Lee and Farhoomand, 1967;McDowell and Humphreys, 2002;Nakata et al, 2001;Vesíc and Clough, 1968;Wissler and Simmons, 1985;Wong and Baud, 1999;Zhang et al, 1990;Zoback and Byerlee, 1976]. Experiments on sand aggregates and sandstones have shown that the amount of compaction obtained at a given effective pressure generally increases with increasing porosity (8) and increasing grain size (d) [Borg et al, 1960;Chuhan et al, 2002Chuhan et al, , 2003Dunn et al, 1973;Hangx et al, 2010;Karner et al, 2005;Lambe and Whitman, 1969;Lee and Farhoomand, 1967;McDowell and Humphreys, 2002;Nakata et al, 1999;Vesíc and Clough, 1968;Zhang et al, 1990]. This is in accordance with the observation that with increasing porosity and grain size, the critical pressure for grain crushing P cr decreases, i.e., the rock becomes weaker [Karner et al, 2005;Wong and Baud, 1999;Zhang et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations